Synthesis and Characterization of Cu, Nd, Ce, Chitosan-Codoped TiO2 Nanoparticles by Sol-Gel Method for Stain Resistance Cotton Fabric Application - Yousefi, M.; Ghasemi, S. (Asian Journal of Chemistry, 2012)
In this study, Nd3+, Cu2+ and Ce3+ doped TiO2 and chitosan masked TiO2, TiO2/Nd3+, TiO2/Nd3+/ Cu2+, TiO2/Nd3+/Ce3+ was synthesized by sol-gel method using tetra n-butyl orthotitanate (TBT) as a precursor. The prepared nanoparticles characterized by FT-IR, XRD, SEM-EDS, TEM, TGA. The XRD showed that the major phase of nanocomposite was anatase. The morphology of the TiO2/Nd3+/Cu2+ and TiO2/Nd3+/Ce3+ microsphere was investigated using SEM. The TEM shows that the size of TiO2/Nd3+/Cu2+ and TiO2/Nd3+/Ce3+ were 8-10 nm. IR spectrum and TGA showed that the existence of chitosan. IR spectrum indicated that Ti-O bond formed in the chitosan-TiO2 nano composite. One of the most important applications of nano particle TiO2 in textile industry product of stain resistance cotton fabric. We studied about this effect of nano particle TiO2 on cotton fabric. The results show that cotton fabric treatment with nano particle TiO2 has this property.